The Essence and Logical Aspect of Competency as a Pedagogical Category (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
On the basis of a competent approach, a system of thematic creative exercises and problematic videotapes is formed, aimed at developing creative thinking of future vocational education teachers and preparing them for professional-pedagogical creativity, and they are recommended to be solved. A cluster model and algorithmic map of the development of competency of professional-pedagogical creativity of the future teacher of professional education have been developed and introduced into practice.